A modified Delphi study on establishing a curriculum content structure for the leadership and management competency cultivation for future nurse managers in China. Issue 12 (December 2022) - Xu, Xiaohua; Zhang, Yuxia; Zhou, Ping; Lin, Ying; Pan, Wenyan
Abstract: Background: It is critical to train future nursing managers in advance for the prospective development of healthcare organizations, but a widely recognized curriculum content structure for leadership and management competency development for nurturing future nurse managers was lacking in China. Objective: To establish a curriculum content structure for the leadership and management competency cultivation for future nurse managers in Chinese healthcare setting. Methods: A modified Delphi study was conducted. 22 experts who have in-depth knowledge of nursing leadership and management from 4 main geographical regions in China were included. The initial curriculum content structure was constructed based on a previous qualitative study and two team meetings. Subsequently, a two-round Delphi survey was conducted with 22 panelists in the first round and 19 in the second round. Scores of importance and textual comments were collected and used to judge the achievement of consensus. Results: After the two-round Delphi process, consensus was reached, as each item was rated ≥4 by 84.21–100% of the experts and each one had a coefficient of variance (CV) ≤ 0.174. The finalized curriculum content contains 9 modules and 27 items. Conclusions: This study formed a curriculum content structure for leadership and management competency training for nurses preparing for managerial roles, which contribute to the establishment of a nursing management talent pipeline to meet the needs of healthcare institutions for contemporary nurse managers. Abstract : Nursing leadership; Nursing management; Curriculum content; Future nurse managers; Delphi study.